Interstitial Perfusion Culture with Specific Soluble Factors Inhibits Type I Collagen Production from Human Osteoarthritic Chondrocytes in Clinical-Grade Collagen Sponges. - Nathalie Mayer (PLoS ONE, 2016)
Articular cartilage has poor healing ability and cartilage injuries often evolve to osteoarthritis. Cell-based strategies aiming to engineer cartilaginous tissue through the combination of biocompatible scaffolds and articular chondrocytes represent an alternative to standard surgical techniques. In this context, perfusion bioreactors have been introduced to enhance cellular access to oxygen and nutrients, hence overcoming the limitations of static culture and improving matrix deposition. Here, we combined an optimized cocktail of soluble factors, the BIT (BMP-2, Insulin, Thyroxin), and clinical-grade collagen sponges with a bidirectional perfusion bioreactor, namely the oscillating perfusion bioreactor (OPB), to engineer in vitro articular cartilage by human articular chondrocytes (HACs) obtained from osteoarthritic patients. After amplification, HACs were seeded and cultivated in collagen sponges either in static or dynamic conditions. Chondrocyte phenotype and the nature of the matrix synthesized by HACs were assessed using western blotting and immunohistochemistry analyses. Finally, the stability of the cartilaginous tissue produced by HACs was evaluated in vivo by subcutaneous implantation in nude mice. Our results showed that perfusion improved the distribution and quality of cartilaginous matrix deposited within the sponges, compared to static conditions. Specifically, dynamic culture in the OPB, in combination with the BIT cocktail, resulted in the homogeneous production of extracellular matrix rich in type II collagen. Remarkably, the production of type I collagen, a marker of fibrous tissues, was also inhibited, indicating that the association of the OPB with the BIT cocktail limits fibrocartilage formation, favoring the reconstruction of hyaline cartilage.